A Review Study on Mechanical Properties of Obtained Products by FDM Method and Metal/Polymer Composite Filament Production. (21st November 2020) - Çevik, Ümit; Kam, Menderes
Abstract : In addition to traditional manufacturing methods, Additive Manufacturing (AM) has become a widespread production technique used in the industry. The Fused Deposition Modeling (FDM) method is one of the most known and widely used additive manufacturing techniques. Due to the fact that polymer-based materials used as depositing materials by the FDM method in printing of parts have insufficient mechanical properties, the technique generally has limited application areas such as model making and prototyping. With the development of polymer-based materials with improved mechanical properties, this technique can be preferred in wider application areas. In this context, analysis of the mechanical properties of the products has an important role in the production method with FDM. This study investigated the mechanical properties of the products obtained by metal/polymer composite filament production and FDM method in detail. It was reviewed current literature on the production of metal/polymer composite filaments with better mechanical properties than filaments compatible with three-dimensional (3D) printers. As a result, it was found that by adding reinforcements of composites in various proportions, products with high mechanical properties can be obtained. Thus, it was predicted that the composite products obtained in this way can be used in wider application areas.